Serum neurofilament light chain is a useful biomarker in pediatric multiple sclerosis. Issue 4 (July 2020) - Reinert, Marie-Christine; Benkert, Pascal; Wuerfel, Jens; Michalak, Zuzanna; Ruberte, Esther; Barro, Christian; Huppke, Peter; Stark, Wiebke; Kropshofer, Harald; Tomic, Davorka; Leppert, David; Kuhle, Jens; et al.
Abstract : Objective: To investigate serum neurofilament light chain (sNfL) as a potential biomarker for disease activity and treatment response in pediatric patients with multiple sclerosis (MS). Methods: In this retrospective cohort study, sNfL levels were measured in a pediatric MS cohort (n = 55, follow-up 12–105 months) and in a non-neurologic pediatric control cohort (n = 301) using a high-sensitivity single-molecule array assay. Association of sNfL levels and treatment and clinical and MRI parameters were calculated. Results: Untreated patients had higher sNfL levels than controls (median 19.0 vs 4.6 pg/mL; CI [4.732, 6.911]), p < 0.001). sNfL levels were significantly associated with MRI activity (+9.1% per contrast-enhancing lesion, CI [1.045, 1.138], p < 0.001; +0.6% per T2-weighted lesion, CI [1.001, 1.010], p = 0.015). Higher values were associated with a relapse <90 days ago (+51.1%; CI [1.184, 1.929], p < 0.001) and a higher Expanded Disability Status Scale score (CI [1.001, 1.240], p = 0.048). In patients treated with interferon beta-1a/b (n = 27), sNfL levels declined from 14.7 to 7.9 pg/mL after 6 ± 2 months (CI [0.339, 0.603], p < 0.001). Patients with insufficient control of clinical or MRI disease activity under treatment with interferon beta-1a/b or glatiramer acetate who switched to fingolimod (n = 18) showed a reduction of sNfL levels from 16.5 to 10.0 pg/mL 6 ± 2 months after switch (CI [0.481, 0.701], p < 0.001). Conclusions: sNfL is a useful biomarker for monitoring disease activity and treatment response in pediatric MS. It is most likely helpful to predict disease severity and to guide treatment decisions in patients with pediatric MS. This study provides Class III evidence that sNfL levels are associated with disease activity in pediatric MS.